2019
DOI: 10.1038/s41598-019-54702-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota Development in Early Childhood

Abstract: Early life determinants of the oral microbiota have not been thoroughly elucidated. We studied the association of birth and early childhood characteristics with oral microbiota composition using 16 S ribosomal RNA (rRNA) gene sequencing in a population-based Swedish cohort of 59 children sampled at 6, 12 and 24 months of age. Repeated-measurement regression models adjusted for potential confounders confirmed and expanded previous knowledge about the profound shift of oral microbiota composition in early life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 61 publications
(67 reference statements)
9
41
0
1
Order By: Relevance
“…Although using the V6 region of the 16S rRNA gene provides somewhat less resolution to the species level than other variable regions, our observed changes in salivary microbiome diversity with age are consistent with results of a Swedish study of 90 children sampled at 3, 6, 12, and 24 mo (Dzidic, Collado, et al 2018) and a Swedish study of 59 children sampled at 6, 12, and 24 mo of age (Kennedy et al 2019). Like these studies, we found that the relative abundance of Streptococcus spp.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although using the V6 region of the 16S rRNA gene provides somewhat less resolution to the species level than other variable regions, our observed changes in salivary microbiome diversity with age are consistent with results of a Swedish study of 90 children sampled at 3, 6, 12, and 24 mo (Dzidic, Collado, et al 2018) and a Swedish study of 59 children sampled at 6, 12, and 24 mo of age (Kennedy et al 2019). Like these studies, we found that the relative abundance of Streptococcus spp.…”
Section: Discussionsupporting
confidence: 87%
“…Teng et al (2015) used temporal patterns of the salivary microbiome to predict onset of ECC among children followed from age 4 to 6 y, but studies describing salivary microbiome dynamics from infancy to age 2 y are few. Two Swedish cohorts revealed that the oral microbiome increases in alpha diversity during early childhood and that microbiome composition is associated with breastfeeding and route of delivery (Dzidic, Abrahamsson, et al 2018; Dzidic, Collado, et al 2018; Kennedy et al 2019). To date, there are no similar studies conducted in US high-risk populations.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus was the only genus detected on the first day of life, while, apart from being the most isolated genus, the Streptococcus strains were isolated in every sample from day two onward ( Figure 1 b), suggesting a persistent colonization of the oral cavity by this genus rather than a transitory passage. Our findings are in accordance with previous studies that have shown that Streptococcus is the dominant genus in the oral cavity of newborns [ 41 , 42 , 43 , 44 ]. Our intention to target the primo-colonizing bacteria was motivated by recent reports describing the early life as a pivotal time for determining the susceptibility to develop chronic respiratory diseases such as asthma.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, they revealed a dramatic shift in the oral microbiome composition from 6 to 24 months, coinciding with the introduction of solid foods and with the period of primary tooth eruption, which provide new micro-environments for colonization. Moreover, the similarity with the maternal microbiota increases over time, leading to a more adult-like composition at 24 months (43). Differences in operational taxonomic units of bacterial genera belonging to the Firmicutes phylum were already described between a group of children fed with breast milk and a group fed with formula, combined or not with breast milk (44).…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, with the introduction of breast milk/formula (oral feedings), the gut bacteria have additional stimulus, and later, with weaning to solid foods, a more adult-like microbiota starts to develop, being further dominated by Firmicutes and Bacteroidetes (38,42). The recent investigation by Kennedy et al (43) involving a cohort of 59 children sampled at 6, 12, and 24 months highlighted that birth characteristics, breastfeeding, antibiotic use, and salivary cortisol play a significant role in the development of the oral microbiota in early childhood. In addition, they revealed a dramatic shift in the oral microbiome composition from 6 to 24 months, coinciding with the introduction of solid foods and with the period of primary tooth eruption, which provide new micro-environments for colonization.…”
Section: Discussionmentioning
confidence: 99%